تحليل المماثلة وأسبابها في سورة يس (دراسة تحليلية فونولوجية): Fonotaktik Surat Yasin: Studi kemiripan Fonemik - Karim, Ahmad Fauzun; Muttaqiin, Miftahul; Moh. Hafidurrahman (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
The text of the Qur'an has been of aesthetic value for the recipient since the beginning of its descent, and it challenges people to produce works that are like the Qur'an, and it comes with a religious and ideological dimension, and it is manifested in the praise of miracles and stands out in the linguistic aspect, the Qur'an carries the word or kalam of Allah, so that people are fascinated by it with a text that challenges them and wins over them,  and the composition that we now notice in the Qur'an, which has some harmony of sound, ease of pronunciation, which is called in the study of sound in similarity. With this, we know that they have a lot in common in the Qur'an. This scientific research uses a type of research with qualitative studies and uses descriptive methods. In this study, the researcher uses the descriptive-analytical desk study method, this is conducting research and study of books, articles, or reports related to the problem expressed by the researcher. The results of the study concluded that there are seven types of progressive similarities in Surah Yasin and eighty-seven other types of similarities in it. The reason is the presence of sounds adjacent to it, the presence of sounds adjacent to adjectives or outputs, and the presence of emphasized letters. It is meant for ease of pronunciation, achieving vocal harmony, and saving muscle effort, and this process to influence the change in meaning.